The analysis of socio-political views in the reporting of ICERD ratification / Kock Yoke Leng - Kock , Yoke Leng (2021)
The International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) is a treaty certified by the United Nation (UN) in 1965 advocating to end discrimination against race and the spread of superiority or hatred based on race, colour or ethnic origins so that everyone can live peacefully. However, it became one of the most talked about topics in Malaysia in 2018 creating controversies which some said stirred the harmony of the country. Malaysia, being one of the 14 countries that has not ratified the ICERD treaty perceive it as a threat to the rights of a certain group of people and it is said to be contradicting the Article 153 of Federal Constitution, which\ protects the special entitlement in terms of political and socio-economic advantages of the Malays and natives of Sabah and Sarawak. Uproars and protests precipitated expressing anger and resentment from different groups of political parties and people when the PH government announced their plans to review and ratify ICERD in October 2018. Despite having the Human Rights Commission of Malaysia (SUHAKAM)’s support that recognizing ICERD is the way forward for Malaysia, many have disagreed and the PH government has decided to not ratify the treaty. The issue was viral since the announcement made by P. Waytha Moorthy in October 2018 for a period of time leading to the day of the rally which was organized as a platform to express dissatisfaction towards the ICERD issue. Many newspaper articles were written and published regarding the issue, and hence, this study aims to reveal how The Star and New Straits Times, which are two mainstream Malaysian English print media, have at length presented the views and ideas of the different parties involved. Using a dialectical-relational critical discourse approach and basing on theories on identifying politics and racism the research shows the relationship of racial, social and political voices and the rationalizations for the positions taken. Findings suggest that ICERD was constructed as the discourse of fear, threats and discriminatory against the Bumiputera by the social actors. These are shown through the use of conditionals and modality along with the overlexicalization of vocabulary and structures to intensify the tone of extremity. ICERD is also said to be intimidating, undermining and threatening the minority.